(3ehShYI (B"(3hjcjHjOjG (BWikipedia" (3GdEdcJQhfjI (B:s (3bGYOI eYQajI eJfGejI aj YUQ GdaVGA GdEdcJQhfj (B/s - (3efUhQj(B: (3NGdO NdaGf CMeO(B..s ((3OHj (B:s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj(B:s, 2013)
(3JJejR gPg GdOQGSI HchfgG GdChdi ef fhYgG HGddZI GdYQHjI(B: (3Yf GdehShYI GdEdcJQhfjI (B"(3GdhjcjHjOjG(B" (3MjK de jSHb hCf foTpQJ OQGSI Yf gPg GdehShYI aj GdhWf GdYQHj(B. (3hJYQV GdOQGSI dTQhW GSJNOGe GdehbY(B: (3hMaX Mbhb GdedcjI GdacQjI(B: (3hZjQgG ef GdTQhW GdJj bO JhLH GdeSGAdI GdbGfhfjI (B: (3hJYQV cPdc deTJedGJ ehbY GdhjcjHjOjG Ydi GdUaMI GdQFjSjI hYdi GdUaMGJ GdefHKbI YfgG(B: (3hGdEMGdI Edi ehGbY GdcJQhfjI CNQi JNOe GdeMJhi GdefThQ LRA efg Ydi GdUaMI GdQFjSjI dehbY GdhjcjHjOjG(B. (3hJYQa gPg GdOQGSI GdHGMKjf hGdbQGA HcjajI GdJYGed eY ehbY GdhjcjHjOjG ef MjK GdGWdGY hGdEVGaI hGdGbJHGS hGdJCcO ef eUOGbjI GdeYdheGJ GdeJhaQI Ydi GdehbY(B: (3hGdGTJQGc hGdeTGQcI(B: (3hHjGf GdeRGjG hGdYjhH aj GdGYJeGO GdCcGOjej dgPg GdehShYI(B..s
(3EUOGQGJ CcGOjejI(B..s
Keywords: (3OhGFQ GdeYGQa GdEdcJQhfjI(B..s; (3GdeMJhi GdebOe ef GdeSJNOejf(B..s